The War in the Historical Memory of Nations - N. V. Pavlov (Vestnik MGIMO-Universiteta)
There is no doubt that the most important event of the 20th century was a joint victory of the united front of peoples and states over German fascism. For some that was the victory in the Second World War. For the Russians - the victory in the Great Patriotic War which cost the Soviet Union incredible efforts, enormous sacrifices and material losses. Now when we celebrate the 70thyear since that epoch-making date we turn our attention once more to the lessons of history because the memory of the war has been imprinted deeply on our gene level of Russians and Germans. This is because every family from both sides sustained heavy losses. This memory is alive in literature, in movies and plays, songs, in memorials, biographies and historical dates. The Russian and German descendants of those who fought against each other are doing an important work searching for the killed, looking after the burial places, compensating the damage to the victims of this inhuman massacre, trying to understand critically our common and controversial past. What was the 9th of May for the Germans and the Russians in the perception of Germans and Russians? Was it a victory, a defeat or liberation? This is what the author of the article reflects on, convinced that we are anyway dealing with the greatest event of the 20th century, at least because it prevented the end of civilization.